2018
DOI: 10.1007/s00586-018-5547-7
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous cement discoplasty for the treatment of advanced degenerative disk disease in elderly patients

Abstract: Percutaneous discoplasty can result as an alternative minimal invasive strategy for the treatment of advanced degenerative disk disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 18 publications
3
55
0
Order By: Relevance
“…This treatment is based on the concept of polymethyl methacrylate (PMMA) injection in the disc space in advances stages of degeneration with vacuum phenomenon, acting as a stabilizer intervertebral spacer, this treatment has demonstrated low back and leg pain improvement and partial correction of spinal balance in unbalanced cases with low complication rates and short hospital stay. [9][10][11] Yamada et al 23 reported improvement in low back pain in 109 patients with degenerative lumbar scoliosis treated with percutaneous intervertebral-vacuum polymethylmethacrylate injection (PIPI), although the name of the procedure differs, the concept is the same. A proper patient selection is necessary, with correct identification of the pain source and some image characteristics may contribute to decrease the risk of some complications such as adjacent vertebral fracture, cement leakage, or disc material protrusion associated with PMMA injection.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment is based on the concept of polymethyl methacrylate (PMMA) injection in the disc space in advances stages of degeneration with vacuum phenomenon, acting as a stabilizer intervertebral spacer, this treatment has demonstrated low back and leg pain improvement and partial correction of spinal balance in unbalanced cases with low complication rates and short hospital stay. [9][10][11] Yamada et al 23 reported improvement in low back pain in 109 patients with degenerative lumbar scoliosis treated with percutaneous intervertebral-vacuum polymethylmethacrylate injection (PIPI), although the name of the procedure differs, the concept is the same. A proper patient selection is necessary, with correct identification of the pain source and some image characteristics may contribute to decrease the risk of some complications such as adjacent vertebral fracture, cement leakage, or disc material protrusion associated with PMMA injection.…”
Section: Discussionmentioning
confidence: 99%
“…34 In recent years, the discoplasty technique has been reported. Varga et al 43 and Carlos Sola et al 44 published their experiences with UC-PMMA as a stand-alone intervertebral spacer (percutaneous cement discoplasty in the case of vacuum phenomenon within lumbar intervertebral discs). They proved the feasibility of percutaneous discoplasty again.…”
Section: Discussionmentioning
confidence: 99%
“…For a detailed description of the procedure see the technical note previously described by the authors. 14 …”
Section: Methodsmentioning
confidence: 99%
“…Discoplasties were performed under general intravenous anesthesia, with patients positioned in a frame with 2 rolls plus an inflatable roll under the thigh region, this roll was insufflated or deflated in order to increase or decrease lumbar lordosis and disc space height. Under fluoroscopic vision and neurophysiological monitoring, according to the technique previously described by Varga et al 12 with modifications by the authors, 14 a Jamshidi cannulated needle was placed at each compromised intervertebral disc. Polymethylmethacrylate (PMMA) (Kyphon HV-R Bone Cement) was slowly injected through the cannula with special attention to detect any sign of cement leakage into the canal or the foraminal space.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation